PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA KHATULISTIWA PONTIANAK - B31111146, Muhammad Isnaeni (Jurnal Manajemen Update, 2016)
The goal of this research was to determine the influence of the working environment on employee’s performance. The method used to prove the hypothesis in this study is a survey using a questionnaire and observation as a data collection instrument. This study consists of two variables: the working environment as independent variable (X1) and motivation (X2). The dependent variable is employee’s performance (Y). The samples in this study were 30 employees. Data managed by using SPSS 16.0 to determine the level of significance using multiple linear regressions. The results of this research as follows: there is influence of the working environment on employee’s performance of PDAM Tirta Khatulistiwa Pontianak, with a contribution of 2.553 (t-test), significant level of 0.17, a constant value of 104,216. There is no influence of motivation on employee’s performance of PDAM Tirta Khatulistiwa Pontianak with a contribution of 0.591 (t-test) significant levels of 0,559, a constant value of 104.216. While the amount of the influence of the working environment and motivation on employee’s performance PDAM Tirta Khatulistiwa Pontianak, with a contribution of 3.392 (F test), significant level of 0.49.     Keywords: working environment, employee’s motivation and employee’s performance